cho Sn3 =(2-can 3)^n+(2+can 3)^n voi n nguyen duong a) cmr :S3n = Sn^3-3Sn b) Tinh S1;S2;S3 12/09/2021 Bởi Charlie cho Sn3 =(2-can 3)^n+(2+can 3)^n voi n nguyen duong a) cmr :S3n = Sn^3-3Sn b) Tinh S1;S2;S3
Đáp án: Giải thích các bước giải: a) Đặt $ a = 2 – \sqrt[]{3} ; b = 2 + \sqrt[]{3}$ $ ⇒ ab = (2 – \sqrt[]{3}). (2 + \sqrt[]{3}) = (2² – \sqrt[]{3}²) = 1$ $ ⇒ S_{n} = a^{n} + b^{n}$ $ ⇒ S_{3n} = a^{3n} + b^{3n} = (a^{n})³ + (b^{n})³ $ $ = (a^{n} + b^{n})³ – 3(ab)^{n}(a^{n} + b^{n}) = S_{n}³ – 3S_{n}$ b) $S_{1} = (2 – \sqrt[]{3})^{1} + (2 + \sqrt[]{3})^{1} = 4$ $S_{2} = (2 – \sqrt[]{3})^{2} + (2 + \sqrt[]{3})^{2} = 14$ $S_{3} = S_{3.1} = S_{1}³ – 3S_{1} = 4³ – 3.4 = 52$ Bình luận
Đáp án:
Giải thích các bước giải:
a) Đặt $ a = 2 – \sqrt[]{3} ; b = 2 + \sqrt[]{3}$
$ ⇒ ab = (2 – \sqrt[]{3}). (2 + \sqrt[]{3}) = (2² – \sqrt[]{3}²) = 1$
$ ⇒ S_{n} = a^{n} + b^{n}$
$ ⇒ S_{3n} = a^{3n} + b^{3n} = (a^{n})³ + (b^{n})³ $
$ = (a^{n} + b^{n})³ – 3(ab)^{n}(a^{n} + b^{n}) = S_{n}³ – 3S_{n}$
b)
$S_{1} = (2 – \sqrt[]{3})^{1} + (2 + \sqrt[]{3})^{1} = 4$
$S_{2} = (2 – \sqrt[]{3})^{2} + (2 + \sqrt[]{3})^{2} = 14$
$S_{3} = S_{3.1} = S_{1}³ – 3S_{1} = 4³ – 3.4 = 52$